A novel and highly efficient earth-abundant Cu3P with TiO2 "P–N" heterojunction nanophotocatalyst for hydrogen evolution from water. Issue 40 (28th September 2016) - Yue, Xinzheng; Yi, Shasha; Wang, Runwei; Zhang, Zongtao; Qiu, Shilun
Abstract : Novel hybrid structure of noble-metal-free p-Cu3 P/n-TiO2 demonstrates excellent photocatalytic hydrogen generation activity due to the high separation and low recombination of photo-generated electron-hole pairs. Abstract : Semiconductor-based photocatalytic hydrogen (H2 ) evolution from water is of great importance for solar-to-chemical conversion processes to boost and promote the future hydrogen economy. Here, for the first time, we demonstrate that p-Cu3 P coupled with n-TiO2 forms a novel hybrid structure which accelerates electron–hole pair separation and transfer for improved photocatalytic H2 -evolution activity. The rate of H2 evolution of the optimized Cu3 P/TiO2 (7940 μmol h −1 g −1 ) is 11 times higher than that of bare TiO2, with an apparent quantum efficiency (AQE) of 4.6%. This work may provide more insight into the synthesis of novel phosphide-based hybrid materials with high photocatalytic H2 -evolution activity and sufficient stability for solar-to-chemical conversion and utilization.